Determinan Profitabilitas Dengan Rasio Pinjaman Terhadap Simpanan Sebagai Variabel Moderasi - Rahman Sastrawan; Edi Saputra; Nia Pratiwi (Department of Accounting, Faculty of Economics & Business, 2023)
The establishment of a banking company can improve the economy and people's welfare. Banking companies distribute funds to the public in the form of loans, so that economic activity runs well. Banking companies also have the main goal of increasing profits or profitability by measuring the value of Return on Assets (ROA). Profitability can be influenced by several factors, namely, Non Performing Loans (NPL) and Capital Adequacy (CAR). The purpose of this study is to see how much influence NPL and CAR have on profitability (ROA): Loan to Deposit Ratio (LDR) as a moderating variable. Secondary research data is in the form of financial statements of publicly listed companies (Tbk) of public and government private banks registered with the Financial Services Authority (OJK) in the 2019-2021 period, using a purposive sampling technique. Hypothesis testing uses the WarpPLS application with the Structural Equation Modeling (SEM) approach. The results showed that NPL had a significant negative effect on ROA, while CAR had a positive effect on ROA. LDR does not moderate NPL and CAR on the profitability of banking companies. This research is useful as a reference for research in the field of accounting, as well as providing information in making investment decisions in a banking company.